ANALISIS RENDAHNYA KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN FISIKA DI SMA NEGERI 10 MEDAN - Agustiani Simbolon; Merry E.Lumbantobing; Roulina Purba; Mariati Purnama Simanjuntak (STKIP Subang, 2026)
Critical thinking skills are an important competency in the 21st century, but they have not yet developed optimally in physics learning in high school. This study aims to analyze students' critical thinking skills at SMA Negeri 10 Medan based on six Facione indicators: interpretation, analysis, evaluation, inference, explanation, and self-regulation. The study used a descriptive qualitative method with one physics teacher and 29 students of class XI F1 selected by purposive sampling. Data were collected through observation, semi-structured interviews, and a critical thinking skills test in the form of 10 conceptual essay questions based on physics phenomena. The results showed that students' critical thinking skills were in the moderate category with an average score of 66.5. The evaluation indicator obtained the highest score (70.5), while the analysis indicator received the lowest (61). Self-regulation is still classified as low-moderate because students are not yet accustomed to reflecting on their thinking processes independently. This condition is influenced by the dominance of lecture methods and the suboptimal use of technology in learning. The study recommends the implementation of innovative learning models such as Problem Based Learning and Inquiry Training to improve students' critical thinking skills.